Reflecting on a Difficult Past Does Not Influence Pro-Environmental Attitudes or Behaviours - Higgins, Kieran; Kilpatrick, Claire (European Journal of Sustainable Development, 2022)
Successfully addressing the environmental crisis requires current generations to change behaviours for the benefit of future generations. Perceptions of responsibility towards future generations have been found to increase pro-environmental attitudes and behaviours. Therefore, methods which enhance feelings of responsibility, or intergenerational reciprocity, are central to tackling the environmental crisis. Research shows intergenerational reciprocity can be increased through the process of reflecting on the heroic actions and sacrifices of past generations. However, the impact of reflecting on a negatively framed ‘difficult’ past remains unknown. Via an online, quasi-experimental questionnaire, this study utilised the context of the ethno-nationalist conflict in Northern Ireland, known as ‘The Troubles’, to explore how reflecting on a difficult past influences pro-environmental attitudes and behaviours. The results suggest that reflecting on The Troubles has no effect on pro-environmental attitudes or behaviour. The salience of negative feelings about The Troubles may have supressed the generation of intergenerational reciprocity and environmental concern